Characterization of the Mechanism and Substrate of Atrial Tachycardia Using Ultra‐High‐Density Mapping in Adults With Congenital Heart Disease: Impact on Clinical Outcomes. Issue 4 (19th February 2019) - Mantziari, Lilian; Butcher, Charles; Shi, Rui; Kontogeorgis, Andrianos; Opel, Aaisha; Chen, Zhong; Haldar, Shouvik; Panikker, Sandeep; Hussain, Wajid; Jones, David Gareth; Gatzoulis, Michael A.; Markides, Vias; et al.
Abstract : Background: Atrial tachycardia (AT) is common in patients with adult congenital heart disease and is challenging to map and ablate. We used ultra‐high‐density mapping to characterize the AT mechanism and investigate whether substrate characteristics are related to ablation outcomes. Methods and Results: A total of 50 ATs were mapped with ultra‐high‐density mapping in 23 procedures. Patients were followed up for up to 12 months. Procedures were classified to group A if there was 1 single AT induced (n=12) and group B if there were ≥2 ATs induced (n=11 procedures). AT mechanism per procedure was macro re‐entry (n=10) and localized re‐entry (n=2) in group A and multiple focal (n=6) or multiple macro re‐entry (n=5) in group B. Procedure duration, low voltage area (0.05–0.5 mV), and low voltage area indexed for volume were higher in group B (159 [147–180] versus 412 [352–420] minutes, P <0.001, 22.6 [12.2–29.8] versus 54.2 [51.1–61.6] cm 2, P =0.014 and 0.17 [0.12–0.21] versus 0.26 [0.23–0.27] cm 2 /mL, P =0.024 accordingly). Dense scar (<0.05 mV) and atrial volume were similar between groups. Acute success and freedom from arrhythmia recurrence were worse in group B (100% versus 77% P =0.009 and 11.3, CI 9.8–12.7 versus 4.9, CI 2.2–7.6 months, log rank P =0.004). Indexed low voltage area ≥0.24 cm 2 /mL could predict recurrence with 100% sensitivity and 77% specificity (area under the curve 0.923, P =0.007). Conclusions: Larger low voltage area but not dense scar is associated with the induction of multiple focal or re‐entry ATs, which are subsequently associated with longer procedure duration and worse acute and midterm clinical outcomes.